Intestinal epithelium-derived BMP controls stem cell self-renewal in Drosophila adult midgut - Aiguo Tian; Jin Jiang (eLife, 2014)
Stem cells are maintained in a specialized microenvironment called niche but the nature of stem cell niche remains poorly defined in many systems. Here we demonstrate that intestinal epithelium-derived BMP serves as a niche signal for intestinal stem cell (ISC) self-renewal in Drosophila adult midgut. We find that BMP signaling is asymmetric between ISC and its differentiated daughter cell. Two BMP ligands, Dpp and Gbb, are produced by enterocytes and act in conjunction to promote ISC self-renewal by antagonizing Notch signaling. Furthermore, the basement membrane-associated type IV collagens regulate ISC self-renewal by confining higher BMP signaling to ISCs. The employment of gut epithelia as a niche for stem cell self-renewal may provide a mechanism for direct communication between the niche and the environment, allowing niche signal production and stem cell number to be fine-tuned in response to various physiological and pathological stimuli.